Perbandingan latihan plyometrics dengan aerobik terhadap memori - Yohana Novelia Christin; Yuriz Bakhtiar; Hardian Hardian; Endang Kumaidah (RSUP Dr. Kariadi, 2021)
ABSTRACT Background: Problems of a person's desire to exercise is still a major highlight in the realm of health, both in Indonesia and in the world. Lack of exercise affects brain work, which is a smaller brain volume in people who are not actively exercising, so doing plyometrics and aerobic exercises can be a solution to these problems because exercise can be easily done for health and increased cognitive abilities. Aim: To understand which exercises are more effective at improving one's short-term memory. Methods: This study is a quasi-experimental study with 54 subjects, all of whom are students of the Faculty of Medicine Diponegoro University, aged between 15-25 years. Subjects were divided into three groups, namely the plyometrics group, the aerobic group and the control group. Subjects were selected by purposive sampling method and participated in the measurement of short-term memory at the time before exercise and after exercise for 6 weeks. Statistical analysis in this study using paired t-test and independent t-test. Results: There was a significant difference in the short-term memory measurement results between the treatment and control groups, but a higher increase was found in the plyometrics group, with p value <0.001. Conclusion: Plyometrics and aerobic exercises improve short-term memory in students of the Faculty of Medicine Diponegoro University. A more significant improvement was found in the plyometrics group. Keywords: plyometrics exercise, aerobic exercise, short term memory.